Rizpah: The church coram Deo - Theron, J (Nederduitse Gereformeerde Teologiese Tydskrif, 2007)
The theme of guilt and the role of the church in a violent society is the focus of this paper. Grappling with sin and its consequences is one of the vocations of the church. More than being legally and ethically responsible to earthly law, the church has to come face to face with God’s eternal law and the devastation of our guilt. The Russian author, Dostoyevski, and the Dutch theologian, Noordmans, contribute to the discussion. This theme is relevant to the whole church, but is specifically applied to the search for unity between the Dutch Reformed Church and the Uniting Reformed Church in South Africa today.